Islamic Education Teachers' Efforts In Fostering Students' Religious Character: A Case Study At Amaliyah Islamic High School - Abdi Syahrial Harahap; Muhammad Yunan Harahap; Sakban Lubis; Fadli Nurul Ikhsan (ASIAN PUBLISHER, 2024)
Religious character is one aspect of human personality that cannot stand alone, meaning that it is related to aspects of personality and must be trained in children as early as possible so as not to hinder the child's further developmental tasks. This ability is acquired by willingness, and encouragement from others. The goal of education is to build character, while the main goal of education is not knowledge but appearance or action. Therefore, character education in an educational institution is very important and necessary. Character education is the process of instilling certain characters as well as providing seeds so that students are able to grow their distinctive characters when running their lives. This research uses a type of qualitative research with descriptive methods. Educators or teachers in the context of character education can play five roles. First, conservator (preserver) of values that are the source of maturity norms. Second, innovator (developer) of science values. Third, transmitting values to students. Fourth, transformer (translator) of values through his/her personality and behavior in interaction with target students. Fifth, organizer (organizer) of the creation of an educational process that can be accounted for both formally (to those who appoint and assign) and morally (to the target students and God who created them). The form of implementing religious programs, namely flash boarding school activities, prayers in congregation, prayers together, reading and writing the Qur'an, blessed Friday activities, extra religious, Islamic studies, khotmil Qur'an events, annual religious activities and the creation of a religious atmosphere at school.